Performance of Novel Contact Stabilization Activated Sludge System on Domestic Wastewater Treatment - Torres Franco, Andrés Felipe (2015)
A pilot-scale study was conducted to evaluate a traditional contact stabilization activated sludge system (CSASC) and a modified CSAS (CSASM) treating domestic wastewater. The CSASC system was comprised of a contact reactor (CR), a stabilization reactor (SR) and a secondary settler(SS); the CSASM included a second CR, a second SS (CR2 and SS2), and a modified SR (SRM) divided into four zones: an attached-suspended growth zone which allowed the system to reach an average sludge retention time close to 36 d and favored the occurrence of nitrification; an anoxic zone for denitrification occurrence; an aerated suspended growth zone with a high presence of organic carbon; and an additional aerated suspended growth zone with a high ammonia concentrations environment. The CSASC’s removal efficiencies of chemical oxygen demand (COD) and total ammonia nitrogen (TAN) were respectively 94±4 % and 53±12%; whereas CSASM’s efficiencies were 88±7% for COD and 92±7% for TAN. Concentrations of TAN and NO3 --N in the CSASC’s final effluent were 14.3±5.2 and 5.0±2.9 mg×L-1; and 4.8±4.4 and 9.1±5.8 mg×L-1 in the CSASM’s final effluent. Results demonstrated that the proposed configuration obtained higher nitrogen removal efficiencies than traditional CSAS.